The Effect of Oil Palm Empty Fruit Bunches on Rice Production (Oryza sativa L.) With a Flood Height of 10 Cm Below Soil Surface - Arman Effendi (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
Improper processing of rice field systems and lack of organic matter in the soil to meet the nutrient needs of rice plants resulted in low rice production. Increased production of rice plants can be overcome by giving compost of palm oil empty fruit bunches (TKKS) with the system of rice intensifications (SRI) method, because the organic matter contained in the compost can improve the physical properties of the soil. This study aims to obtain the best dose of empty fruit bunch (EFB) compost and to see its effect on the production of lowland rice (Oryza sativa L.) by using the modified SRI method. The research was conducted from January-April 2019 at the UPT Experimental Garden, Faperta, Riau University. This study applied a completely randomized design (CRD) consisting of 5 treatment levels. They are 0 gr.polybag-1, 50 gr.polybag-1, 75gr.polybag-1, 100 gr.polybag-1 and 125 gr.polybag-1. The results showed that giving empty fruit bunch (EFB) compost with the SRI method gave an effect on productive tillers, pithy grain per panicle and grain weight, but did not affect panicle exit age, harvest age, percentage of pithy grain per panicle and 1000 grain weight of pithy grain. The best treatment dose was found at a dose of 20 ton.ha-1 because it could increase several components of lowland rice production of the Batang Piaman variety.